BUDGET PARTICIPATION: INTERACTION EFFECTS OF WORK ENGAGEMENT AND EMPOWERMENT - Chia, Yew-Ming, Dr; GRANT, Lewis, Mr (Jurnal Akuntansi dan Keuangan Indonesia, 2023)
This study investigates the two-way interaction effects of work engagement and empowerment on the degree of employees' budget participation industry in Scotland. Data are collected from 159 employees via an online questionnaire and analyzed using multiplicative regression analysis. The results confirm the presence of a two-way interaction effect between work engagement and empowerment on the degree of budget participation at a statistically significance level (p = 0.0002). Further analysis indicates that the higher the empowerment, the greater its enhancing effect on the positive relationship between work engagement and the degree of employees' budget participation. This study provides one of the first empirical evidence of a contingent relationship between work engagement and budget participation over the range of the level of empowerment. Consequently, the results have contributed insights to the literature in facilitating our understanding of both the moderating role of empowerment and extending the boundary conditions on work engagement and budget participation association. Human resource personnel and management can consider the application of empowerment as a potential intervention strategy to boost the productivity and performance of employees resulting from the latter's increased participation in the budget-setting process.